Analisis Pengaruh Harga dan Kualitas Produk pada Keputusan Pembelian di PT Mandom Indonesia Tbk (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of price and product quality on purchasing decisions for personal care products manufactured by PT Mandom Indonesia Tbk. The topic was chosen in response to increasingly intense competition in the cosmetics industry, along with a decline in sales performance of several Mandom products, which highlights the need for the company to better understand key factors affecting consumer purchasing behavior. The research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 100 respondents who use Mandom products, selected through purposive sampling. Prior to analysis, the research instruments were tested for validity and reliability to ensure the accuracy and consistency of the data. The data were then analyzed using multiple linear regression techniques. The results indicate that price has a positive and significant effect on purchasing decisions and is the most dominant influencing factor. This finding suggests that consumers place strong emphasis on the suitability between price and perceived benefits when making purchasing decisions. Product quality also shows a positive and significant influence, although its effect is relatively smaller compared to price. Simultaneously, price and product quality explain a portion of the variation in purchasing decisions, while other factors outside the study also contribute. Based on these findings, PT Mandom Indonesia Tbk is advised to prioritize competitive pricing strategies while consistently maintaining product quality to enhance purchase intentions and strengthen consumer loyalty.